The Debate of Orthodox Sufism and Philosophical Sufism: The Study of Maqāmāt in the Sirāj al-Ṭālibīn of Shaykh Iḥsān Jampes - Syamsun Ni'am (Al-Jami'ah Research Centre, 2020)
This article discusses the mystical view of Shaykh Iḥsān Jampes Kediri, East Java. He is known as a muslim jurist as well as a practical Sunnī Sufi of Nusantara (Indonesia), with a worldwide reputation. The main reason for his reputation originates from his monumental work Sirāj al-Ṭālibīn a voluminous commentary of al-Ghazālī work, Minhāj al-’Ābidīn, which had successfully reaffirmed orthodox Sunnī sufism that built and developed by al-Ghazālī. The sufism attitudes and ways of Shaykh Iḥsān in the journey were as if dealing with a sufi group which had philosophical pattern. Additionally, Shaykh Iḥsān Jampes in Sirāj al-Ṭālibīn reviewed the sufistic core stages which are called maqāmāt by many sufis, but Shaykh Iḥsān calls them steep road (‘aqabah) consisting of seven steep stages. These differences bring some consequences not only on the number of steps/stairs/maqām and the final destination of his mystical journey, namely gnosis and deification; but also question the limit of human being who physically cannot be united with God. On the other hand, God could have chosen to be invited to unite in accordance with His will. These seven ‘aqabah are to deliver a traveller towards ma’rifatullāh (gnosis) as the ultimate mystical journey.[Artikel ini membahas pandangan sufistik Syaykh Iḥsān Jampes Kediri Jawa Timur. Ia adalah ahli hukum Islam yang juga sebagai praktisi sufi sunni yang terkenal di nusantara kala itu. Alasan utama yang membuatnya diperhitungkan adalah karyanya Sirāj al-Ṭālibīn yang berupa komentar terhadap Minhāj al-’Ābidīn karya al-Ghazālī. Sikap dan jalan sufi Shaykh Iḥsān Jampes tampaknya bersepakat dengan pola sufistik falsafati. Dalam karyanya tersebut ia membahas tingkatan yang oleh para sufi biasa disebut maqāmāt, dimana ia sendiri menyebutnya dengan jalan terjal (‘aqabah) yang terdiri dari 7 tingkatan. Perbedaan ini tidak hanya membawa perbedaan konsekuensi jumlah tangga dan tujuan akhir (gnosis dan deification), tapi juga soal batasan kemampuan fisik manusia untuk menyatu dengan Tuhan. Di sisi lain, Tuhan dapat juga mengundang untuk bersatu berdasarkan kehendakNya. Tujuh tingkatan ‘aqabah inilah yang akan membawa para musafir menuju ma’rifatullāh sebagai puncak perjalanan spiritual.]